Entrepreneurial universities and integrated sustainability for the knowledge-based economy: self-perception and some structural challenges in the Gulf region - Esmat Zaidan (16855203) (2024)
Innovation and the promotion of entrepreneurship are requirements of the transition towards knowledge-based economies. Universities are assigned a key role in advancing entrepreneurship through the restructuring of teaching, research, and governance with an emphasis on innovation and sustainability. In the Gulf region, universities are increasingly adopting reforms aimed at redefining their missions towards entrepreneurial education. This study examines the impact of university-based innovation and entrepreneurial models on progressing towards knowledge-based economies, with Qatar University serving as a case study. It qualitatively assesses recent university reforms and contextualizes these reforms within limitations in the national context and the political economy of the rentier states in the Gulf. The findings suggest that for Gulf region universities to effectively become entrepreneurial and support sustainable development, they must cultivate an entrepreneurial culture and mindset. This requires structural and cultural shifts that resonate with national context, institutional values, and the global sustainability goals. The study indicates that a top-down approach to developing entrepreneurial universities is less effective. It advocates for policies and incentives that motivate universities to become entrepreneurial. Ultimately, the study’s insights aim to guide policymaking to develop knowledge economy frameworks in Qatar towards a sustainable future. Other Information Published in: Humanities and Social Sciences Communications License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1057/s41599-024-03032-2